TINJAUAN YURIDIS PELAKSANAAN PENYELESAIAN KREDIT MACET PADA BANK RAKYAT INDONESIA CABANG SLEMAN AKIBAT ERUPSI GUNUNG MERAPI DI KABUPATEN SLEMAN - , DIYAH NURIZA ARIFNOVIYANI; , Prof. Dr. Abdul Ghofur Ansori, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study is to discover the implementation process the completion of bad debt and to know the assurance position in completion of bad debt at Bank BRI Sleman due to the eruption of Mount Merapi in Sleman. This study was an empirical juridical law to obtain primary data about related matters that exist in the field and the materials which related to the research topic as secondary data. The primary data was obtained by interviews and secondary data was obtained from books or literatur for theoretical explanation of the law related to this study. The data collection method in this study was used by the literature research and interviews. The research results obtained qualitatively analyzed with descriptive methods. The results showed that (1) implementation process the completion of bad debt due to the eruption of Mount Merapi in District Sleman which identified the condition of customers by bank and then further efforts of 3R which consisting of rescheduling, reconditioning and restructuring. Rescheduling is changes in credit terms realtingti the payment schedule and/or the time term. Reconditioning is change some or all of the credit terms are not limited to changes in the payment schedule , duration , and other terms along or not relating to changes in the maximum credit balance . Restructuring that changes the terms of bank credit in the form of additional funding and / or conversion of all or part of the interest arrears into a new loan principal , in addition to the efforts of the Bank also provides loans partnerships. (2) In case of assurance position in completion of bad credit due to the eruption of Mount that the letter of assurance ownership remain in bank until the loan will bepaid off and there is no execution of loan assurances by the bank because the completion of bad credit conditions caused by natural disasters.